Perancangan Sistem Pengendali Suhu Untuk Optimalisasi Daya Panel Surya Menggunakan Logika Fuzzy - Wifki Ato'ur Rochim; Wijaya Kurniawan; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Solar energy can be used as a potential alternative energy. One of them is the usage of solar panels that can convert sunlight into electrical energy. In the use of solar panels have several factors that can affect the ability to convert solar energy. One influencing factor is the temperature of the panel. Electrical energy generated by the panel will be more optimal if the panel is at 25Â°C or below. To optimize the conversion of solar energy by solar panels, a system that can control the temperature is needed to keep the panel at normal temperature. To fulfill that requirement the author designed a solar panel temperature control system consisting of two LM35 temperature sensors applied to the bottom of the panel and a DC motor as a fan or panel cooler. Arduino Uno used as a microcontroller with fuzzy logic program therein to determine the speed of fan rotation refers to the result of temperature captured by temperature sensor. Fuzzy logic is choosen because it has advantages over other methods, which are easy to understand, flexible, tolerant of improper data, capable of modelling complex nonlinear function, able to work with conventional control techniques, and provide excellent control. From the result of test that have been done found that this system can optimize temperature cooling time of the solar panel by 9 minutes 22 second compared without using temperature control system.